Chiari malformation may increase perivascular cerebrospinal fluid flow into the spinal cord: A subject-specific computational modelling study. (8th December 2017) - Lloyd, Robert A.; Fletcher, David F.; Clarke, Elizabeth C.; Bilston, Lynne E.
Abstract: Syringomyelia is associated with Chiari I malformation, although the mechanistic link is unclear. Studies have suggested that cerebrospinal fluid enters the spinal cord via the perivascular spaces, and that changes in the timing of the subarachnoid pressures may increase flow into the spinal cord. This study aims to determine how Chiari malformation and syringomyelia alter the subarachnoid space pressures and hence perivascular flow. Subject-specific models of healthy controls (N = 9), Chiari patients with (N = 7) and without (N = 8) syringomyelia, were developed from magnetic resonance imaging (MRI), to simulate the subarachnoid pressures. These pressures were input to an idealised model of the perivascular space to evaluate potential differences in perivascular flow. Peak pressures in Chiari patients without a syrinx were higher than in controls (46% increase; p = .029) and arrived earlier in the cardiac cycle than both controls (2.58% earlier; p = .045) and syrinx patients (2.85% earlier; p = .045). The perivascular model predicted Chiari patients without a syrinx would have the greatest flow into the cord (p < .05) if the arterial pulse delay was between 4 and 10% of the cardiac cycle. Using phase-contrast MRI the mean arterial delay for all subjects was similar, and was estimated as 4.7 ± 0.2%. The perivascular pumping rate showed a strong positive correlation ( R Adj 2 = 0.85 ; p < .0001) with extended periods of high pressure that arrived earlier in the cardiac cycle, suggesting these pressure characteristics may play a role in syrinx development.